Can we reduce oxidative stress with liver transplantation? oxidative stress in cirrhosis and after transplantation - Aydin, Mesut (Journal of Medical Biochemistry, 2021)
Background: The aim of this study was to determine the levels of lipid peroxidation (MDA) and antioxidants such as reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) in the blood serum of patients with cirrhosis and liver transplantation.Materials and Methods: In this study, serum malondialdehyde acid (MDA) levels, superoxide dismutase (SOD), reduced glutathione (GSH), and catalase (CAT) activities were measured spectrophotometrically and compared to the results of the healthy control group.Results: SOD, CAT and GSH activities were significantly decreased in the patient groups compared to the healthy control group (p
Keywords: oxidative stress, cirrhosis, liver transplantation